Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

S’approprier son genre entre pathologie et résistance. La transidentité après la Révolution islamique en Iran - Azadi, Bahar (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2020)
https://journals.openedition.org/cedref/1361
Keywords: asie; corps; cours; fem3400; identités LGBTQIA2+; iran; islam; personnes trans*; premier cycle; ressource en ligne; régions géographiques; thématiques

Queer China: Lesbian and gay literature and visual culture under postsocialism - Bao, Hongwei (Routledge, Taylor & Francis Group, 2020)
Ce livre analyse la production culturelle queer dans la Chine contemporaine pour cartographier les vastes transformations sociales en matière de genre, de sexualité et de désir. Il examine la littérature queer et les cultures visuelles de l'ère post-Mao et postsocialiste de la Chine pour montrer comment ces diverses formes et pratiques culturelles fonctionnent non seulement comme des formes d'activisme social spécifiques au contexte et culturellement sensibles, mais produisent également des types distincts de subjectivités de genre et sexuelles propres à Les conditions postsocialistes de la Chine. De la poésie à l'art du découpage de papier, de la « littérature camarade/gay » aux fanfictions amoureuses entre filles, des films lesbiens aux documentaires activistes, et d'un spectacle de dragsters à Shanghai à une représentation publique d'un mariage homosexuel à Pékin, le livre révèle une Chine queer dans toute sa complexité idéologique et son énergie créatrice. Riche empiriquement et méthodologiquement éclectique, Queer China tisse habilement la recherche historique et archivistique, l'analyse textuelle et discursive, ainsi que les entretiens et l'ethnographie. Innovant et mettant en avant une perspective non occidentale, ce travail transdisciplinaire contribue à de multiples domaines académiques, notamment les études littéraires et culturelles, les études sur les médias et la communication, les études cinématographiques et cinématographiques, l'art contemporain, les études de théâtre et de performance, les études de genre et de sexualité. , études Chine/Asie et pays du Sud, histoire culturelle et géographie culturelle, théorie politique et étude des mouvements sociaux.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; chine; cinéma; communication; discipline; queer; régions géographiques

Voix et travail des femmes dans les développements touristiques à Hampi - Biddle Bocan, Charlotte (Université du Québec à Montréal, 2020)
Cette recherche partira des points de vue des femmes qui travaillent dans les infrastructures touristiques de Hampi pour comprendre les développements touristiques dans cette région. À la lumière des propos énoncés par les personnes participantes à une recherche terrain, nous analyserons les enjeux politiques et sociaux provoqués par ces développements touristiques. Cette recherche a donc trois objectifs (1) mettre de l’avant les points de vue de celles, ceux qui ne sont pas entendues dans un discours dominant sur les développements touristiques (2) de comprendre ces développements touristiques à partir du point de vue de celles, ceux qui les vivent au quotidien, qui travaillent au sein de ces infrastructures touristiques et, partant de leurs voix (3) démontrer les implications sociales et politiques des restructurations suscitées par ces développements touristiques en remettant en question la littérature néolibérale et hégémonique sur les développements touristiques. Cette recherche répond à la question suivante : comment les développements touristiques à Hampi sont expliqués, organisés et revendiqués par les populations de basses castes et classes qui travaillent dans les infrastructures touristiques du village ? Nous verrons que les femmes considèrent le tourisme comme une opportunité afin de mieux répondre à leurs besoins et à ceux de leur communauté, toutefois l’importance grandissante que prendra le tourisme dans le village entrainera l’implication d’acteurs urbains et supranationaux qui déstabilisent l’organisation du travail des femmes et de leurs communautés entrainant tranquillement leur exclusion du village. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : tourisme, néolibéralisme, travail des femmes, capitalisme, développement, Inde
Keywords: IREF; asie; discipline; inde; mémoires/thèses; néolibéralisme; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques; tourisme; travail; travail des femmes*

The missing doctors — An analysis of educated women and female domesticity in Pakistan - Mohsin, Mariam; Syed, Jawad (Gender, Work and Organization, 2020)
While the percentage of female students in medical schools in Pakistan is as high as 80–85 per cent, the percentage of female doctors in the medical workforce remains below 50 per cent. Our findings draw on in-depth interviews with 31 female doctors to show that the reasons behind the gap between female medical students and female medical professionals are multifold and multilayered, ranging from individual reasons to organizational and sociocultural reasons. We use an adapted version of the relational framework developed by Syed and Özbilgin in 2009 to offer a contextual and multilevel understanding of female domesticity in Pakistan. The study suggests that the problem of female doctors dropping out of the medical workforce is a reflection of the interplay of social, organizational and individual factors, which are tied together by social norms. Practical implications suggest that making hospitals and health organizations more inclusive of women and their needs could be a starting point for policymakers to address the gender gap in the medical profession. © 2020 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; asie; conciliation famille-travail; famille; femmes* médecins; maternité; pakistan; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Benefits and constraints of the agricultural land acquisition for urbanization for household gender equality in affected rural communes: A case study in Huong Thuy Town, Thua Thien Hue Province, Vietnam - Thi, Nhung Pham; Kappas, Martin; Wyss, Daniel (Land, 2020)
Le gouvernement vietnamien a mis en œuvre l'acquisition de terres agricoles pour l'urbanisation (ALAFU) depuis 2010, ce qui a provoqué un niveau élevé de transition socio-économique dans le pays. Dans cet article, nous avons appliqué l'approche genre et développement pour découvrir comment l'ALAFU a influencé l'égalité des sexes au sein des ménages dans les zones touchées de la province de Thua Thien Hue, au Vietnam. Les données de cet article ont été principalement collectées à partir de deux enquêtes auprès de groupes de ménages, de quatre discussions de groupe et de six entretiens avec des informateurs clés. Le groupe 1 couvre 50 ménages affectés dont les terres agricoles ont été acquises pour l'urbanisation, tandis que le groupe 2 se compose de 50 ménages dont les terres agricoles n'ont pas été confisquées. Les résultats révèlent que l'ALAFU a conduit à un accès réduit aux terres agricoles pour le groupe 1, mais a contribué à une augmentation du statut économique des femmes des deux groupes en créant des opportunités d'emploi non agricoles avec un bon revenu. Cependant, la plupart de leurs nouveaux emplois sont encore informels, comportent des risques potentiels et la charge de travail de soins non rémunérés est lourde. De plus, bien que le taux de participation des femmes à la prise de décision au sein du ménage ait augmenté, la qualité de la participation est limitée. Leur participation aux activités sociales et aux cours de formation professionnelle s’est améliorée de manière insignifiante. Par conséquent, si le Gouvernement continue de promouvoir l’ALAFU, il devra prendre en compte les inégalités structurelles entre les sexes pour atteindre ses objectifs de développement durable.
Number: 8
Keywords: 2000 à aujourd'hui; 2010-2019; asie; care; participation citoyenne des femmes; projet charge mentale; périodes historiques; régions géographiques; terres agricoles; thématiques; travail; travail du care; urbanisation; vietnam

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Work-family balance and the subjective well-being of rural women in Sichuan, China - Yue Shui; Xu, Dingde; Liu, Yi; Liu, Shaoquan (BMC Women's Health, 2020)
Background Due to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.Methods This study used a sample survey of 380 rural women in rural areas of Sichuan Province to measure rural women’s cognition of work-family, coordination and handling of conflicts, post-conflict choices, and subjective well-being; the study constructs an ordered multi-class logistic regression model to explore the impact of work-family conflict on the subjective well-being of rural women in rural regions.Results The study result shows that: (1) The level of subjective well-being of rural women is generally high, and 70% of women feel satisfied or very satisfied. (2) The factor which impacts the subjective well-being among rural women most is work-interfering-with-family conflict, followed by work-family balance and confidence in conflict coordination.Conclusion This study can enhance our understanding of rural women in rural areas, and provide a reference for formulating policies to improve people’s life satisfaction.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; bien-être psychosocial; chine; conciliation famille-travail; famille; femmes rurales; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail